Көркем әдебиятымызда әдеплилик үлгилери - Утегенова, Ж.Ж (SCIENCE and SOCIETY, 2017)
The article is devoted to the description of the national values and the best gualities of the Karakalpak people that have been kept since ancient time: kindness, humanity, fried ship and love to Mother land on the material of extracts from the works of fiction.
Keywords: national value; ancestors; Motherland; literature; poems; friendship